Three-Month Follow-Up on Successful Treatment in a Cervical Cancer Patient with Chemoradiation Partial Response: A Case Report - Saputra, Rudi; Andriansyah, Andriansyah; Ruslim, Samuel Kelvin; Raharjo, Eko Nugroho (http://dharmais.co.id/, 2025)
Introduction: The choice of therapy for cervical cancer strongly relies on the cancer stage. Stage IIB cervical cancer entails radiation therapy and chemotherapy, excluding surgery due to the risk of serious complications. This case is particularly interesting for discussion as the patient underwent a radical hysterectomy, bilateral salpingo-oophorectomy, and pelvic lymph node dissection following chemoradiation, resulting in a partial response.Case Presentation: A 56-year-old woman presented with a complaint of continuous, progressive clear, and odorless fluid discharge from her birth canal, diagnosed with cervical cancer grade IIB. The patient underwent three cycles of cisplatin chemotherapy and radiation at a total dosage of 70.4 Gy over 38 sessions. Post-chemoradiation evaluation revealed a residual tumor with a diameter of 2 cm, and the patient underwent a radical hysterectomy, bilateral salpingooophorectomy, and pelvic lymph node dissection.Conclusion: Surgery post-chemoradiation for cervical cancer in centers that don’t have any brachytherapy can be considered as an option, yielding positive effects with minimal side effects. Healthcare centers with limitations in brachytherapy can utilize EBRT boosters, which may be continued with surgery depending on the patient’s response to the earlier therapy.